2008
DOI: 10.1016/j.memsci.2008.04.059
|View full text |Cite
|
Sign up to set email alerts
|

High performance nitrile copolymers for polymer electrolyte membrane fuel cells

Abstract: a b s t r a c tThis paper reports the fuel cells (DMFC and PEMFC) performance using sulfonated poly(arylene ether ether nitrile) (SPAEEN) copolymers containing sulfonic acid group arranged in structurally different ways. The membrane electrode assembly (MEA) fabricated from SPAEEN containing 60 mol% of angled naphthalenesulfonic acid group (m-SPAEEN-60) had superior performance over those derived from pendent naphthalenesulfonic acid group (p-SPAEEN) or sulfonated hydroquinone (HQ-SPAEEN) in H 2 /air and/or DM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(46 citation statements)
references
References 31 publications
(56 reference statements)
1
45
0
Order By: Relevance
“…Furthermore, SPAEEN with sulfonic acid groups meta to the ether linkage (m-SPAEEN) and those with sulfonic acid groups located pendant on a phenyl ring (P-SPAEEN) exhibited much higher proton conductivities because the meta linkage and the long-distance connectivity of their sulfonic acid groups, could eliminate deactivation of the sulfonic acid groups, respectively [90]. As a result, m-SPAEEN membranes showed high performance in both PEMFC and DMFC fuel cell applications [106,107]. The authors also explained the effect of the angled structure, which increased the interchain spacing and created pores with sulfonic acid groups within.…”
Section: Introduction Of Functional Groupsmentioning
confidence: 99%
“…Furthermore, SPAEEN with sulfonic acid groups meta to the ether linkage (m-SPAEEN) and those with sulfonic acid groups located pendant on a phenyl ring (P-SPAEEN) exhibited much higher proton conductivities because the meta linkage and the long-distance connectivity of their sulfonic acid groups, could eliminate deactivation of the sulfonic acid groups, respectively [90]. As a result, m-SPAEEN membranes showed high performance in both PEMFC and DMFC fuel cell applications [106,107]. The authors also explained the effect of the angled structure, which increased the interchain spacing and created pores with sulfonic acid groups within.…”
Section: Introduction Of Functional Groupsmentioning
confidence: 99%
“…A highly fluorinated main-chain in the sPAE series provides a high degree of chain hydrophobicity and chemical stability to the materials. 9 In our previous study, 26 it was shown that the introduction of nitrile groups into sulfonated copolymers of specific structures reduced the water uptake (wt %) and dimensional swelling (vol %). The present sPAEN contains an unprecedented high content of phenylnitrile groups for an experimental PEM material.…”
Section: Resultsmentioning
confidence: 96%
“…We suggest that a plausible factor for the low water uptake of copolymers containing nitrile groups is the presence of strong nitrile dipole interchain interactions occurring in certain polymer structural configurations that combine to limit swelling in water. 23,26 In addition, nitrile-sulfonic acid group interactions also appear to be important, as nitrile groups have been found to associate with sulfonic acid groups through bridging water molecules in specific spectroscopic studies. Table 2 also shows the proton conductivity of the present sPAE and sPAEN PEMs and Nafion that were measured on free-standing membranes.…”
Section: Resultsmentioning
confidence: 99%
“…Also, hydrocarbon-based polymer membranes have been demonstrated for fuel cell operations with a Nafion binder in the catalyst layers. [4][5][6][7][8][9][10][11][12][13][14] However, the systems containing Nafion binder exhibited poor interfacial compatibility between the membrane and electrodes. 4 Therefore, the use of hydrocarbon-based polymers as binders in the catalyst layer is emerging as a new area of research.…”
Section: Introductionmentioning
confidence: 99%